Social Policies for Inclusive Development in Vietnam - Hà, Mai; Tuyên, Hoàng Văn; Trường, Đào Thanh (VNU Journal of Science: Policy and Management Studies; Vol 32 No 1, 2016)
Abstract: Nowadays, each country has been facing several crucial issues in development which come from both subjective and objective aspects, most prominent were (1) solutions to sustainable poverty reduction while the poverty rate remains high, (2) difficulties in applying the scientific and technical advances in production process because of low – level of literacy in rural and mountainous areas, (3) disadvantaged group meets the challenges in accessing to social resources, especially educational opportunities, (4) attracting social investment in agriculture, rural areas and farmers is very limited due to the low profit generated from this area, despite of being counted for more than 60% of population, and mostly (5) challenges in policy proposal and implementation process for sustainable regional development. In order to absolutely deal with those challenges, Vietnam has been using government policies as the main macro approach along with other micro ones. This study selected key policies for each problem, considering how the government recognized and addressed them, as well as the main findings. Although each policy tackled different major aims, they all highly focus on issues relate to innovation, sustainable poverty reduction,  improve the quality of workers, mobilize social resources for program on the socio- economic development. Additionally, a case study of a program which has been launched since 1998 nationwide was presented in the second part of the study, providing an in-depth analysis on socio – economic aspects with some given recommendations for inclusive development inVietnam. Keywords: social policies, regional development, technology transfer